A discursive pragmatic approach to the third person pronoun ta in Chinese computermediated communication. (7th December 2019) - Sluchinski, Kerry
Abstract : This study examines the persuasive discourse of institutional accounts on Sina Weibo which contains the genderless non-standard third person pronoun ta written in the Roman alphabet instead of standard Chinese characters. Mandarin Chinese originally used the single character 他 (ta) to refer to the third person 'he', 'she', and 'it', which later gave way to three separate written 'standard' forms: ta 他 'he', ta 她 'she', and ta 它 'it' all with the same pronunciation. From a discourse analysis perspective, the study incorporates the 'three-move structure' textual analysis methodology to shed light on both contemporary language use and one of the most under-studied interpersonal dialogic practices in Chinese computer-mediated communication: ta. The research shows that the environments in which ta appears are associated with two main goals: (1) generating monetary profit and (2) generating engagement with services/ideologies.